Quality of life in peritoneal dialysis patients and its relationship with nutrition disorders - Dudar, I.; Shymova, A.; Gonchar, Y.; Loboda, O.; Krasiuk, E. (Ukrainian Journal of Nephrology and Dialysis, 2019)
Abstract. The aim of our study was to evaluate the quality of life (QoL) in peritoneal dialysis (PD) patients and its relationship with nutritional disorders. Methods. 52 PD patients were included in the observational cross-sectional study. The QoL was conducted using a SF-36 quality of life assessment questionnaire. Moreover, the PD patients’ nutrition status (NS) was examined. For further analysis, the patients were divided into four groups according to the condition of the NS: the first group (n = 22) consisted of patients without nutrition disturbance, the second group (n =13) included the patients with mild nutrition disorders, the third group (n = 10) consisted the patients with an average degree of the NS, and the fourth one (n = 7) envolved the patients with a severe degree of malnutrition. A comparative evaluation of QoL among the PD patients with different nutrition disorders was performed. Results. During the analysis of indicators QoL we receive the following results: all patients were dissatisfied with the general state of health, the lowest of the indicators was the burden of the disease. The physical total component was lower than the mental. According to the analysis of NS parameters, nutritional disorders were observed in 57.6 % patients. Also according to the results, it follows that nutritional disorders negatively affect the QoL of the PD patients. Moreover, a direct strong correlation between the serum albumin level and the overall QoL score was obtained (r = 0.95; p < 0.001). In addition, the strong direct correlation between a body mass index (BMI) and overall QoL (r = 0.92; p < 0.001) and subjective global assessment (SGA) and overall QoL (r = 0.85; p < 0.001) were observed. Conclusions: According to the results of the study, it was found that PD patients’ QoL is dissatisfied. It was confirmed that nutritional disorders affect bad on the QoL of patients with almost all parameters. The overall QoL was significantly associated with serum albumin levels, BMI and SGA.